An exegesis of bacteriophage therapy: An emerging player in the fight against anti-microbial resistance (2020)
Bacteriophages (simply referred to as Phages) are a class of viruses with the ability to infect and kill prokaryotic cells (bacteria), but are unable to infect mammalian cells. This unique ability to achieve specific infectiousness by bacteriophages has been harnessed in antibacterial treatments dating back almost a decade before the antibiotic era began. Bacteriophages were used as therapeutic agents in treatment of dysentery caused by Shigella dysenteriae as far back as 1919 and in the experimental treatment of a wide variety of other bacterial infections caused by Vibrio cholerae, Staphylococcus sp., Pseudomonas sp. etc, with varying degrees of success. Phage therapy and its many prospects soon fell out of favour in western medicine after the Second World War, with the discovery of penicillin. The Soviet Union and other countries in Eastern Europe however mastered the craft of bacteriophage isolation, purification and cocktail preparation, with phage-based therapeutics becoming widely available over-the-counter. With the recent rise in cases of multi-drug resistant bacterial infections, the clamour for a return to phage therapy, as a potential solution to the anti-microbial resistance (AMR) crisis has grown louder. This review provides an extensive exposé on phage therapy, addressing its historical use, evidences of its safety and efficacy, its pros and cons when compared with antibiotics, cases of compassionate use for treating life-threatening antibiotic-resistant infections, the limitations to its acceptance and how these may be circumvented.